Examination of polytrauma typologies: A latent class analysis approach. (September 2017) - Sullivan, Erin; Contractor, Ateka A.; Gerber, Monica M.; Neumann, Craig
Abstract: Potentially traumatizing events (PTE) are highly prevalent, and are associated with detrimental effects on psychological health, including increased risk of posttraumatic stress disorder (PTSD). Multiple endorsed PTEs (polytraumatization) may have even greater effects on a person's health than the impact of a single index event. To better understand patterns of polytraumatization, person-centered analytic techniques such as Latent class analysis (LCA) are recommended. The current study used LCA to explore latent subgroupings of people based on their endorsement of PTEs, thus defining patterns in PTE exposure. The sample included 850 participants who endorsed at least one PTE on a web-administered Trauma History Questionnaire (THQ). Results indicated a best-fitting 3-class solution: (1) a class with a greater probability of experiencing interpersonal PTEs and other PTEs, (2) a class with moderate PTE exposure and higher probability of mugging and accidents, and (3) a class with low PTE exposure. Differences in age, gender, and PTSD symptom severity accounted for class membership. Results suggest the experience of interpersonal PTEs may be a risk factor for additional lifetime PTE exposure, and is associated with increased PTSD severity. Additional findings underscore the heterogenity of trauma experiences, highlighting the importance of examining such patterns in future research. Highlights: LCA identified 3 subgroups of participants based on traumatizing events (PTEs). Class 1 had the highest frequency of PTEs, and greatest interpersonal PTE exposure. Classes 2 and 3 had moderate and low PTE exposure, respectively. Age, gender, and PTSD severity predicted group membership. Findings highlight the importance of examining trauma type and frequency.